Life cycle assessment (LCA) of apples - Johansson, Davida (2015)
Agricultural greenhouse gas emissions have great impact on climate change and need to be reduced. The production and transport of food accounts for up to 25% of total greenhouse gas emissions. Life cycle assessment (LCA) can be used to measure Global Warming Potential (GWP) between production systems and transports to identify sources of greenhouse gas emissions. In this study, GWP was measured as carbon dioxide equivalents (CO2eq) and was calculated for Swedish IP-certified apples, Swedish organic certified apples (KRAV), IP-certified apples imported from Italy and IP-certified apples imported from Argentina. The system boundaries were 1) production, 2) sorting, packaging and cold storage, 3) transport to retailer. Production of Swedish IP apples had lowest emission of CO2eq compared to Swedish organic and Italian IP. Diesel consumption was a major source of CO2eq emissions in the production, independent of production system. Swedish IP-certified apples stored for 3 months had much lower CO2eq emissions than imported apples transported directly at harvest from Italy and Argentina by truck and boat. It is CO2 efficient to increase the market share of Swedish apples if storage time is less than 12 months, as CO2eq emissions are lower than imported apples from Italy and Argentina.